Postpartum dietary intake, depression and the concentration of docosahexaenoic acid in mature breast milk in Wuhan, China. Issue 5 (13th February 2023) - Cao, Yuan; Wei, Qiaosi; Zou, Li; Jiang, Shilong; Deng, Haichao; Jiang, Chuqi; Cui, Ningning; Huang, Shanshan; Ge, Yanyan; Li, Yan; Tan, Le; Guo, Shu; et al.
Abstract : Breast milk DHA proportion was positively associated with maternal aquatic product intake and DHA supplement use, and negatively associated with postpartum depression status. Abstract : Background : Docosahexaenoic acid (DHA, C22:6) is an important fatty acid in breast milk and is essential for infantile growth and cognitive development. However, the factors that affect the DHA concentration in breast milk have not been completely clarified. Objective : This study aimed to characterize the composition of breast milk fatty acids and to identify maternal factors associated with breast milk DHA concentration in postpartum women in Wuhan, China. Methods : In this cross-sectional study, we analyzed milk fatty acids in 115 lactating women at 30–120 days postpartum using GC-MS. Maternal sociodemographic, health and other information were collected using a self-reported questionnaire. Maternal dietary intake information was collected through a 24-hour dietary recall method. Postpartum depression status was identified using the Edinburgh Postnatal Depression Scale (EPDS). Results : The mean DHA proportion in breast milk was 0.49%. The multivariate regression model showed that the milk DHA proportion was positively associated with maternal aquatic product intake ( β = 0.183, 95%CI: 0.052, 0.314) and DHA supplement use ( β = 0.146, 95%CI: 0.108, 0.185), and negatively associated with postpartum depression status ( β = −0.122, 95%CI: −0.243, −0.002) after adjustment for several maternal and infant factors. Conclusion : Increasing maternal aquatic product intake and DHA supplement use and improving postpartum depression status may increase DHA concentration in breast milk in lactating women.